(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Heterocyclic scaffolds maintain their structural variety and bioactivity, which is encouraging in the continuous search for powerful antifungal medicines. Based on the 5,5-dihydrothiadiazolo-[3,2-a]- [1,3,5]-triazin-5-one core structure, this paper introduces a new series of fused five- and six-membered heterocyclic compounds and details their design, synthesis, and biological assessment. The suggested molecular frameworks were validated by characterizing the produced compounds using conventional spectroscopic methods, such as infrared, nuclear magnetic resonance, and mass spectrometry. A battery of phytopathogenic and clinically significant fungal species, including Aspergillus niger, Candida albicans, Fusarium oxysporum, and Trichophyton rubrum, were subjected to an extensive in vitro fungicidal screening. The findings showed that some compounds have broad-spectrum fungicidal action, with minimum inhibitory concentrations (MICs) that were on par with or higher than those of conventional antifungal medications. Investigations into the structure-activity relationship (SAR) showed that the antifungal effectiveness was improved by adding electron-withdrawing substituents to the triazine portion. These results show that 5,5-dihydrothiadiazolo-[3,2-a]-[1,3,5]-triazin-5-ones are a good starting point for developing novel broad-spectrum fungicides that are both effective and safe to use.